Makna Kodrat Alam Ki Hajar Dewantara dalam Tren #KaburAjaDulu Bagi Gen Z - Chumairoh, Malikah; Pratiwi, Poerwanti Hadi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study aims to examine the relevance of Ki Hajar Dewantara’s concept of kodrat alam (the law of nature) with the social media phenomenon #KaburAjaDulu, which has recently gained popularity among Indonesia’s Generation Z. The research employed a qualitative content analysis using a critical discourse analysis approach, drawing data from 50 online news articles discussing the hashtag.The finding sreveal that #KaburAjaDulu originated from the disappointment and protest of young people toward government policies perceived as unfavorable to the public particularly those involving budget cuts in education and health sectors to fund new programs with uncertain outcomes. This phenomenon reflects a social reality in which many young Indonesians choose to work or pursue education abroad, believing such opportunities to be more promising and adequate. Based on Ki Hajar Dewantara’s concept of kodrat alam, this condition indicates a mismatch between individuals’ potential and their social environment, which should ideally serve as a space for self-development. Therefore, the government needs to promote programs that foster self-recognition and personal potential among students to enhance their competitiveness and contribution within the country. Through such efforts, individuals can discover their talents and meaningful career paths in Indonesia, without feeling the need to “escape” abroad.